PENDIDIKAN KARAKTER DISIPLIN DI LINGKUNGAN SEKOLAH - Maskuri, Maskuri (IAIIG Cilacap, 2018)
The character education of discipline within the scope of the school is the effort of giving guidance to the learners in order to have self control to comply with all rules and regulations that exist, and avoid any deviations and violations that can harm both students and schools as a whole, which is expected it can applied also in everyday life. In this case, the main purpose of disciplined character education for learners is not to provide fear or restraints, but to educate learners in order to organize and control themselves in behaving. To realize all it is necessary to the process of planting the character of discipline in school. If speaking embeds a character, then a method is needed. The method of discipline character education that can be invested in schools include: the method of habituation as the main method, which is then supported by several other methods such as: punishment method; exemplary methods; methods of advice; methods of observation and supervision; methods of advice, orders and restrictions; methods of praise and rewards; as well as methods of reprimands, warnings, and threats.